“My Heart and My Brain Is What's Bleeding, These Are Just Cuts.” An Interpretative Phenomenological Analysis of Young Women's Experiences of Self-Harm - Norman, Hilary; Marzano, Lisa; Oskis, Andrea; Coulson, Mark (Frontiers in Psychiatry, 2022)
Engagement in self-harm, defined as intentional self-poisoning or self-injury irrespective of the apparent purpose of the act, is increasing, particularly among girls and young women. Understanding the behaviour from the perspective of those who self-harm is, therefore, vital in designing effective interventions and treatments. The current brief research report presents a key theme from an Interpretative Phenomenological Analysis of the experience of self-harm among eight young women, aged between 18 and 29. The theme Is Self-Harm Bad? concerns the way in which participants both acknowledged and resisted a negative conception of self-harm that was often constructed from other people’s attitudes. Three subthemes explore the reasons why participants were reluctant to endorse self-harm as bad: Self-Harm is the Symptom, Self-Harm Works (Until it Doesn’t) and Self-Harm is Part of Me. The findings highlight the disparity between the characterisation of self-harm as a highly risky behaviour and the lived experience of self-harm as a functional means of emotion regulation. From a clinical perspective, the findings suggest that highlighting the risks of self-harm may not be a sufficient deterrent. The recently revised draft National Institute for Health and Care Excellence (NICE) guidance recommends that everyone presenting to hospital following self-harm should be given a comprehensive psychosocial assessment, of which the function is, in part, to understand why the person has self-harmed. The current study underlines the importance of seeing past the behaviour to the underlying causes and exploring the meaning of self-harm to the individual in order to implement effective preventative interventions.